EVALUASI PROGRAM PENGUJIAN KENDARAAN KELILING OLEH DINAS PERHUBUNGAN KOTA DENPASAR - Yoni Enjels, Ni Kadek; Winaya, I Ketut; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2020)
ABSTRACT The Denpasar City of Department of transportation is one of the institutions in Bali Province that apply the testing transportation using pick-up service system. The application ofathis systemais aimed toamakeaeasierafor theapeopleato testatheir vehicleaandareduce the traffic jam in technical implementation unit. The innovation of this program begun in 2016.However, in its application thereaareastillaproblemsarelatedato the lackaof socialization and uneven cars of testing in Denpasar. Thisaresearchauseda qualitativeadescriptiveamethodatheadataacollectionatechniquesaareaobservation,interview and documentation. It is showed from six criterias that used for that system, it still faces some problems for each indicators.Related to the effectiveness of vehicle testing, time efficiency, human resource efficiency, adequacy in overcoming vehicle queue problems and employee responsiveness. Key words : Evaluation, Service, Testing Transportation Using Pick up Service System